Effect on security of supply of renewable energy penetration in an electricity market: risks, opportunities, and challenges (2017)
As the electricity industry is changing worldwide with the advent of renewable energy sources such as solar and wind power, so the major concerns of policy makers are now security of supply and electricity prices to consumers. The new industry conditions of intermittency, seasonality, global-climate - variation and their effect on security of supply increase problem complexity, making difficult the task of pursuing three conflicting goals in the power industry: security of supply, competitive prices and environmental protection. In this context, and given the multiple uncertainties in power supply, most notably the technology transformation, this study uses modelling-based scenario analysis to investigate different, extreme, though plausible futures. System dynamics has been considered for the analysis of policy aimed at increasing the enetration of renewables and to explore how these energy sources may affect system reliability. Our study concludes that for the Colombian case, the large hydroelectric component has led to high olatility, thereby increasing the risk to capacity investment. Though not intuitive at first glance, renewable energies will stabilise the system in the medium-term by reducing price volatility (except when there is a very high level of installed renewables), and increasing security of supply, given their energy complementarity